What Is the Influence of Simulation-Based Training Courses, the Learning Curve, Supervision, and Surgeon Volume on the Outcome in Hernia Repair?—A Systematic Review - Köckerling, Ferdinand (Frontiers in Surgery, 2018)
Introduction In hernia surgery, too, the influence of the surgeon on the outcome can be demonstrated. Therefore the role of the learning curve, supervised procedures by surgeons in training, training courses and surgeon volume on patient outcome must be identified. Materials and Methods A systematic search of the available literature was carried out in June 2018 using Medline, PubMed and the Cochrane Library. For the present analysis 75 publications were identified as relevant. Results Well-structured training courses were found to be associated with a reduced perioperative complication rate for patients operated on by trainees. Open as well as, in particular, laparo-endoscopic hernia surgery procedures have a long learning curve. Its negative impact on the patient can be virtually eliminated through consistent supervision by experienced hernia surgeons. However, this presupposes availability of an adequate trainee caseload and of well-trained hernia surgeons and calls for a certain degree of centralization in hernia surgery. Conclusion Training courses, learning curve, supervision and surgeon volume are important aspects in training and outcomes in hernia surgery